Macrophage‐derived MLKL in alcohol‐associated liver disease: Regulation of phagocytosis. Issue 3 (17th March 2023) - Wu, Xiaoqin; Fan, Xiude; McMullen, Megan R.; Miyata, Tatsunori; Kim, Adam; Pathak, Vai; Wu, Jianguo; Day, Le Z.; Hardesty, Josiah E.; Welch, Nicole; Dasarathy, Jaividhya; Allende, Daniela S.; et al.
Abstract : Background and Aims: Mixed lineage kinase domain‐like pseudokinase (MLKL), a key terminal effector of necroptosis, also plays a role in intracellular vesicle trafficking that is critical for regulating liver inflammation and injury in alcohol‐associated liver disease (ALD). Although receptor interacting protein kinase 3 (Rip3) −/− mice are completely protected from ethanol‐induced liver injury, Mlkl −/− mice are only partially protected. Therefore, we hypothesized that cell‐specific functions of MLKL may contribute to ethanol‐induced injury. Approach and Results: Bone marrow transplants between Mlkl −/− mice and littermates were conducted to distinguish the role of myeloid versus nonmyeloid Mlkl in the Gao‐binge model of ALD. Ethanol‐induced hepatic injury, steatosis, and inflammation were exacerbated in Mlkl −/− →wild‐type (WT) mice, whereas Mlkl deficiency in nonmyeloid cells (WT→ Mlkl −/− ) had no effect on Gao‐binge ethanol‐induced injury. Importantly, Mlkl deficiency in myeloid cells exacerbated ethanol‐mediated bacterial burden and accumulation of immune cells in livers. Mechanistically, challenging macrophages with lipopolysaccharide (LPS) induced signal transducer and activator of transcription 1–mediated expression and phosphorylation of MLKL, as well as translocation and oligomerization of MLKL to intracellular compartments, including phagosomes and lysosomes but not plasma membrane. Importantly, pharmacological or genetic inhibition of MLKL suppressed the phagocytic capability of primary mouse Kupffer cells (KCs) at baseline and in response to LPS with/without ethanol as well as peripheral monocytes isolated from both healthy controls and patients with alcohol‐associated hepatitis. Further, in vivo studies revealed that KCs of Mlkl −/− mice phagocytosed fewer bioparticles than KCs of WT mice. Conclusion: Together, these data indicate that myeloid MLKL restricts ethanol‐induced liver inflammation and injury by regulating hepatic immune cell homeostasis and macrophage phagocytosis. Abstract :